Efficiency of using Canephron® N in the treatment of children with secondary hyperoxaluria - T.P. Borysova (Zaslavsky O.Yu., 2017)
Background. The purpose of our work was to study the clinical effectiveness of the application of phytotherapeutic drug Canephron® N for secondary hyperoxaluria in children in combination with diet as compared to the dietary treatment alone. Materials and methods. 46 children aged 6-18 years with secondary hyperoxaluria were examined. Depending on the treatment scheme, patients are divided into groups: the main group (23 children) and the comparison group (23 persons). All children received dietary treatment with the exception of high-oxalic acid foods and sufficient drinking regime. In addition to diet therapy, the patients of the main group were treated with Canephron® N for 3 months. Daily excretion of oxalates, calcium, uric acid, phosphate and calcium/creatinine ratio in the morning urine before treatment and after 3 months of therapy were studied. Results. After 3 months of therapy, there was a decrease in daily excretion of oxalate in urine in both observation groups. The decrease in urinary excretion of oxalate on the background of therapy was more significant in children of the main group than in the comparison group (3.050 ± 0.320 vs. 1.600 ± 0.102, p < 0.001). The incidence of hyperoxaluria on the background of therapy in the main group decreased from 100 to 56.5 % (p < 0.01), in the comparison group it almost did not change (from 100 to 82.6 %, p > 0.05). The incidence of hypercalciuria in both groups did not change. At the same time, the daily excretion of calcium, phosphorus and uric acid in the main group was significantly reduced. In patients of the main group, there was a decrease in the erythrocyturia rate - from 52.2 to 17.4 % (p < 0.01). In patients of the comparison group, this indicator did not change significantly. The level of daily proteinuria before and after the treatment decreased only in children of the main group - from 0.117 g/day to 0.052 g/day (p < 0.02). Conclusions. Using phytotherapeutic drug Canephron® N for three-month therapy of secondary hyperoxaluria in children in combination with dietary treatment is more effective than monotherapy with diet and leads to a 3-time decrease of the oxalate level in urine. Treatment with restriction of high-oxalic acid foods gives the result of not more than 1.6 times. The inclusion of phytotherapeutic drug Canephron® N is accompanied by a 3-fold decrease in the erythrocyturia rate and a reduction of daily proteinuria.